Sierra Summit Football Stadium in Antipolo City, Rizal - Tapucar, Shania C. (College of Architecture, University of the Philippines Diliman, 2023)
This study explores strategies to meet the growing demand for a football stadium in Antipolo, Rizal, located in Eastern Luzon, Philippines. With a focus on accommodating both current and future requirements of players and fans, the research delves into various aspects such as design, capacity, infrastructure, and community engagement. Emphasizing the symbiotic relationship between the stadium and its surrounding site, the study seeks to establish a harmonious integration of function and identity. Focusing on the challenging hilly terrain of Antipolo City, the study explores innovative stadium design principles, by skill-fully integrating topographical features. The research aims to create a harmonious blend between the stadium's functional requirements and the natural landscape. The proposed design not only caters to football enthusiasts in Eastern Luzon but also offers a template for architectural solutions that respect and enhance the environment. By embracing the unique hilly terrain of Antipolo City, the study demonstrates how innovative stadium design can seamlessly accommodate sporting demands while contributing positively to the local identity, economy, and a vibrant football culture for the Philippines.